Gene x environment interactions in conduct disorder: Implications for future treatments - Holz, Nathalie E.; Zohsel, Katrin; Laucht, Manfred; Banaschewski, Tobias; Hohmann, Sarah; Brandeis, Daniel (Neuroscience & biobehavioral reviews, 2018)
Conduct disorder (CD) causes high financial and social costs, not only in affected families but across society, with only moderately effective treatments so far. There is consensus that CD is likely caused by the convergence of many different factors, including genetic and adverse environmental factors. There is ample evidence of gene-environment interactions in the etiology of CD on a behavioral level regarding genetically sensitive designs and candidate gene-driven approaches, most prominently and consistently represented by MAOA. However, conclusive indications of causal GxE patterns are largely lacking. Inconsistent findings, lack of replication and methodological limitations remain a major challenge. Likewise, research addressing the identification of affected brain pathways which reflect plausible biological mechanisms underlying GxE is still very sparse. Future research will have to take multilevel approaches into account, which combine genetic, environmental, epigenetic, personality, neural and hormone perspectives. A better understanding of relevant GxE patterns in the etiology of CD might enable researchers to design customized treatment options (e.g. biofeedback interventions) for specific subgroups of patients.
Available online 18 August 2016
Gesehen am 06.06.2019